Apple whole genome sequences: recent advances and new prospects. Issue 1 (5th April 2019) - Peace, Cameron P; Bianco, Luca; Troggio, Michela; van de Weg, Eric; Howard, Nicholas P; Cornille, Amandine; Durel, Charles-Eric; Myles, Sean; Migicovsky, Zoë; Schaffer, Robert J; Costes, Evelyne; Fazio, Gennaro; et al.
Abstract: In 2010, a major scientific milestone was achieved for tree fruit crops: publication of the first draft whole genome sequence (WGS) for apple ( Malus domestica ). This WGS, v1.0, was valuable as the initial reference for sequence information, fine mapping, gene discovery, variant discovery, and tool development. A new, high quality apple WGS, GDDH13 v1.1, was released in 2017 and now serves as the reference genome for apple. Over the past decade, these apple WGSs have had an enormous impact on our understanding of apple biological functioning, trait physiology and inheritance, leading to practical applications for improving this highly valued crop. Causal gene identities for phenotypes of fundamental and practical interest can today be discovered much more rapidly. Genome-wide polymorphisms at high genetic resolution are screened efficiently over hundreds to thousands of individuals with new insights into genetic relationships and pedigrees. High-density genetic maps are constructed efficiently and quantitative trait loci for valuable traits are readily associated with positional candidate genes and/or converted into diagnostic tests for breeders. We understand the species, geographical, and genomic origins of domesticated apple more precisely, as well as its relationship to wild relatives. The WGS has turbo-charged application of these classical research steps to crop improvement and drives innovative methods to achieve more durable, environmentally sound, productive, and consumer-desirable apple production. This review includes examples of basic and practical breakthroughs and challenges in using the apple WGSs. Recommendations for "what's next" focus on necessary upgrades to the genome sequence data pool, as well as for use of the data, to reach new frontiers in genomics-based scientific understanding of apple. Genetics: Apple genome sequencing begins to bear fruit: Almost 10 years since the first draft of the apple genome was published, the insights it has afforded are being used to improve crops, while next generation DNA sequencing is enabling the breeding value of individual plants to be more rapidly assessed. In this review, Cameron Peace at Washington State University in Pullman, US, and colleagues describe the impact whole genome sequencing of the Golden Delicious apple has had on our understanding of how cultivated apples evolved, and the genomic regions controlling fruit firmness and flavor, tree growth dynamics, responses to water and nutrient availability, and other such traits. These early discoveries have also paved the way for trait-predictive tests which should further accelerate the breeding of improved apple trees, and epigenetic studies to better understand how environmental factors trigger heritable changes in apple characteristics.